Dating game - Steel, Danielle (New York : Bantam Dell, 2004)
Paris Armstrong, devastated when her husband leaves her after twenty-four years of marriage, moves across the country to San Francisco where a less-than-satisfactory dating experience leads her to make some important decisions about the direction of her future.
New York Times.
New York Times, April 2003.
Adult
Keywords: Dating (Social customs) -- Fiction; Divorced women -- Fiction; Dating (Social customs) -- Fiction; Divorced women -- Fiction; Humorous fiction; Love stories; San Francisco (Calif.) -- Fiction; San Francisco (Calif.) -- Fiction; Humorous fiction; Love stories